A study of efficacy of oral iron and intravenous iron sucrose in the treatment of moderate anemia in pregnancy - Prajapati, Saloni M.; Patel, Meha K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Iron deficiency anaemia in pregnancy is a common medical problem throughout India with the burden of disease impacting on both mother and the newborn. It is also responsible for increased incidence of premature births, low birth weight babies and high perinatal mortality. Intravenous iron sucrose and oral iron therapy are the primary therapeutic modalities for management of iron deficiency anaemia during pregnancy, but its efficacy during pregnancy is still a matter of argument among healthcare personnel. Therefore the objective of this study is to compare the effect of oral iron and intravenous iron sucrose on hemoglobin and other blood indices among pregnant females with iron deficiency anemia. Methods: Randomized clinical trial was conducted among 400 females between 20 to 34 weeks gestation with iron deficiency anemia who were managed either with oral ferrous sulphate or intravenous iron sucrose therapy. Z test was used for statistical analysis for significance with 95% confidence interval. The hemoglobin and blood indices levels before and after initiating treatment in both groups were compared. Results: Intravenous and oral; both the treatments were associated with increment in hemoglobin but this rise was significantly more in the intravenous group than in oral. Comparing participants with low pretreatment hemoglobin among both groups, participants in the intravenous group were better benefited than oral due to respective treatment. Conclusions: Intravenous iron therapy is much effective in correcting iron deficiency anemia in pregnancy than oral iron therapy. It restores iron stores more promptly. Also intravenous iron is better tolerated compared to oral iron.